2012
DOI: 10.1007/s00268-012-1563-7
|View full text |Cite
|
Sign up to set email alerts
|

Cosmesis and Body Image after Minimally Invasive or Open Thyroid Surgery

Abstract: Studies in the literature that evaluate body image and cosmesis in thyroid surgery using standardized methods are scarce. In our department, the results of a questionnaire showed that the MI approach has no advantage for body image and cosmesis over the CO approach. Further prospective randomized studies using different tools with a larger sample size are needed to investigate the use of MI procedures for thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 45 publications
0
33
1
5
Order By: Relevance
“…There have been few more previous studies which have derived similar conclusions [2][3][4][5]; however, none have been as extensive as the present study. The sample size is large and very heterogeneous; therefore, there can be many confounding factors which I would like to highlight.…”
contrasting
confidence: 37%
“…There have been few more previous studies which have derived similar conclusions [2][3][4][5]; however, none have been as extensive as the present study. The sample size is large and very heterogeneous; therefore, there can be many confounding factors which I would like to highlight.…”
contrasting
confidence: 37%
“…In the authors' experience only 15% of patients were candidates for the procedure (26). Lower figures (10% or less) have been reported from regions where goitre is endemic (37). Another disadvantage of MIVAT is that despite its satisfying long-term cosmetic outcomes, it is not protective against kelloids (40,41).…”
Section: Mivat's Disadvantagesmentioning
confidence: 83%
“…While this has been demonstrated by many (7,27) studies, others concluded that a shorter cervical scar was not associated with improved patient satisfaction (36)(37)(38). Furthermore, it may be argued that shorter incisions may compromise the safety of a procedure without favorably influencing patient satisfaction (39).…”
Section: Mivat's Advantagesmentioning
confidence: 88%
“…Fiftyseven relevant thyroidectomy papers were identified, twenty of which reported some form of cosmetic outcome assessment. These included 6 randomised controlled trials (RCTs) with 412 patients (evidence level 2B), [6][7][8][9][10][11] 7 cohort studies with 3,073 patients (level 3B) [12][13][14][15][16][17][18] and 7 non-comparative case series with 1,575 patients (level 4). [19][20][21][22][23][24][25] The remaining studies made reference to the issue of cosmesis either by assumption, referencing or general statements unsupported by methodological assessment.…”
Section: Review Resultsmentioning
confidence: 99%